APAKAH UKURAN ITU PENTING? (Studi Empiris pada Prusahaan Manufaktur di Bursa Efek Jakarta tahun 2012-2014) - Ardiansyah Japlani (Akuisisi: Jurnal Akuntansi, 2015)
Stock market is a vital in importance for the economical development of a country. This study aimed to investigate the effect of market capitalization on stock return. Stock return in this study using mean of average stock return for years 2012 to 2014. This study uses comparison between large and small capitalization market. We diviede the sample into two groups, large and small cap. If the market capitalization is more than five trillion, it is categorized as large caps. If the market capitalization is less than one trillion, it is categorized as small cap firms. We found that the small cap firms have a stronger effect on the stock market than large cap firms by using analysis of regression.